A study on the learning spaces of UP students and its implications to the General Reference Section of the UP Diliman Main Library - Orijuela, Sherwin R. (2012)
According to Skiba (2006), a learning space can be a formal space such as classrooms or a learning laboratory or as with the current generation, learning spaces are all locations where learning takes place. In order to stay in step in the evolution of learning spaces, library spaces should be able to adapt to the learning preferences of its users. This study is focused on knowing the current learning spaces of the UP students who are library users of the General Reference Section of the UP Main Library and its relation to the current library spaces of the General References section of the UP Main Library.